If,

5 + 3 – 2 = 48;

4 – 3 + 3 = 28.

Then,

5 + 2 + 3 – 4 + 4 – 3 = ?

0 votes

0 votes

**Answer: 98**

**Explanation:**

If you carefully observe all the equations you will see the pattern in the equations. There are more than one operation that is done to get the resultant number on the right hand side of the equation.

First solve the equations linearly, then take the result and multiply all the positive numbers on the left hand side. Now add the resultant numbers and drop the negative numbers from the equation.

For example in the first equation which is;

5 + 3 – 2 = 48;

Linearly solving them gives you the result: 5 + 3 – 2 = 6

So now multiply all the positive numbers by 6 and drop the negative numbers from the equation on the left hand side;

5 x 6 + 3 x 6 = 30 + 18 = 48

Similarly for 2nd equation;

4 – 3 + 3 = 4;

4 x 4 + 3 x 4 = 16 + 12 = 28

Therefore we see: 4 – 3 + 3 = 28.

Then for the last equation to find the missing number we solve it as,

5 + 2 + 3 – 4 + 4 – 3 = 7

now multiplying 7 to all the positive numbers and dropping the negative numbers we get;

5 x 7 + 2 x 7 + 3 x 7 + 4 x 7 = 35 + 14 + 21 + 28 = 98

**Therefore;
5 + 2 + 3 – 4 + 4 – 3 = 98**

...